2009
DOI: 10.1071/sh09014
|View full text |Cite
|
Sign up to set email alerts
|

The role of drugs during group sex among gay men in Australia

Abstract: Methamphetamine and heavy alcohol use are associated with increased sexual risk behaviour among men who engage in group sex. Within more 'adventurous' gay community subcultures, drug use is often for the explicit purpose of enhancing the sexual experience and this complex relationship may be key to understanding HIV risk among these men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 36 publications
3
77
0
Order By: Relevance
“…Drug use, particularly when used to enhance sexual pleasures has been associated with CLAIC and with incident HIV infection among GBM (Bolding et al, 2006;Buchacz et al, 2005;DiFranceisco, Ostrow, & Chmiel, 1996;Koblin et al, 2003;McCabe, Hughes, Bostwick, West, & Boyd, 2009;Prestage, 2009;Prestage, Grierson, Bradley, Hurley, & Hudson, 2009a;Rusch, Lampinen, Schilder, & Hogg, 2004;Solomon, Kiang, Halkitis, Moeller, & Pappas, 2010). Specigfically, crystal methamphetamine and erectile dysfunctin medication (EDM), both used separately or in combonation, have been most strongly implicated with sexual risk behaviours and HIV infection (Prestage, Jin, Kippaz, Zablotska, Imrine, & Grulich, 2009b;Fisher, Reynolds, & Napper, 2010).…”
Section: Condomless Anal Intercourse With Casual Male Partners (Claicmentioning
confidence: 99%
“…Drug use, particularly when used to enhance sexual pleasures has been associated with CLAIC and with incident HIV infection among GBM (Bolding et al, 2006;Buchacz et al, 2005;DiFranceisco, Ostrow, & Chmiel, 1996;Koblin et al, 2003;McCabe, Hughes, Bostwick, West, & Boyd, 2009;Prestage, 2009;Prestage, Grierson, Bradley, Hurley, & Hudson, 2009a;Rusch, Lampinen, Schilder, & Hogg, 2004;Solomon, Kiang, Halkitis, Moeller, & Pappas, 2010). Specigfically, crystal methamphetamine and erectile dysfunctin medication (EDM), both used separately or in combonation, have been most strongly implicated with sexual risk behaviours and HIV infection (Prestage, Jin, Kippaz, Zablotska, Imrine, & Grulich, 2009b;Fisher, Reynolds, & Napper, 2010).…”
Section: Condomless Anal Intercourse With Casual Male Partners (Claicmentioning
confidence: 99%
“…3,17 These event-level assessments of alcohol use provide the most precise temporal link between these two behaviors and provide stronger evidence for causality. 2,17 Binge drinking and other patterns of heavy alcohol use are independently associated with a variety of high-risk behaviors in MSM, including unprotected anal sex, multiple partners, and having HIV-serodiscordant partners, [18][19][20][21][22][23][24][25][26][27][28] a link also observed among Black, Native American, and older MSM. [29][30][31] Binge drinking and heavy alcohol consumption are major causes of incident HIV infections in MSM.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Prior studies with MSM have also found a strong association between substance use and UAS, yet the casual link between these two behaviors regarding HIV acquisition is much less understood and critically important for HIV prevention. [3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted.…”
Section: Introductionmentioning
confidence: 99%